Out on a limb? : domestic fixed income assets in Australia: Australian Securitisation Forum. - Deloitte Access Economics (Barton, ACT: Deloitte Access Economics, 2012)
"The Australian Securitisation Forum ("the ASF") is pleased to endorse this research report into the factors influencing the allocation of Australia's investment markets to the domestic fixed income asset class and its connection to the current limited scale of the local bond market." --Overview.
"Australian Securitisation Forum : 23 October 2012 ."
Title from screen (viewed on 11 August 2014 )
Includes bibliographical references
Mode of access: Available online. Address as at 11/08/14
Selected for archiving
Keywords: Fixed-income securities -- Australia; Investment funds -- Australia; Securities -- Australia; Finance, Personal -- Australia; Saving and investment -- Australia; Australian